Packaging and acceptability of yam balls (ojojo) among visitors to Agodi gardens in Oyo State, Nigeria (2021)
There is a need to enhance and support the implementation of locally made (indigenous) food items and snacks. This can be done by making them more tasty and presentable. Ojojo is a popular delicacy among the Ijebu tribe of south-west Nigeria, and can be regarded as a savory snack/food. It can be referred to as an underutilized snack due to the fact that it is made from water yam which is underutilized in this part of the world. Indigenous and traditional foods/snacks, if property utilized could help to solve the problem of poverty, hunger and malnutrition locally, and as such could be promoted to global level. The research was carried out in Agodi gardens located in Ibadan, Oyo state. One hundred and one copies of structured questionnaires (sensory evaluation form) were administered to respondents within Agodi gardens using convenient sampling to assess the organoleptic characteristics, different packaging and overall acceptability of ojojo. The questionnaires were analyzed using descriptive statistics (charts and percentage) and inferential statistics (spearman correlation, t-test, and multiple linear regression. Result from nutritional/proximate analysis revealed that ojojo contains moisture (51.4%), protein (5.9%), fat (8.5%), ash (2.9%), crude fibre (1.1%) and carbohydrate (30.2%). The organoleptic characteristic showed that 58.4% of the respondents liked the taste of the sample, and the mean distribution showed that taste (x=7.35) ranked highest. The result for the different packaging materials showed that 85.4% liked the sample being served and 61.4% of the respondents' preferred plastic pack compared to other packaging materials. The level of acceptability showed that ojojo was well accepted by the respondents as 86.1% of the visitors had above the score of 6 (liked slightly) in the sensory attributes evaluated. Different packaging materials affected the level of acceptance of ojojo among visitors to Agodi gardens. Also, the nutritional benefits, taste, aroma, and overall packaging are major predictors of overall acceptability of ojojo.